Are the new generations always revolutionaries? Beliefs and stakes - Burga Díaz, Manuel (2021)
This essay proposes a comparison between two generations, both comprised by young people, some of them quite young, in markedly different contexts: the first one appeared in the 1920-1921 period, during the centennial commemoration of independence; and the second, named Bicentennial Generation, emerged nationwide between the 9 and 15 of November of 2020 with a tragic aftermath, but at the same time achieving significant political success. The former consisting of a seemingly small group of middle-class university students from the countryside manifesting only in Lima, but which developed invisible connections with rural, peasant and revolutionary regions. The latter arises as the driving force of massive, more noticeable, widespread mobilizations, which embraced other generations in their marches and where women played a leading role. These two generations have wondered the same, about building a new country, where they can live happy and well, more democratically, with less discrimination and inequality, more justice and changing almost everything. That is why I wonder: are the new generations always revolutionaries?